PENGARUH PENGGUNAAN TURBO ELEKTRIK DAN SARINGAN UDARA MODIFIKASITERHADAP KADAR EMISI GAS BUANG CO DAN HC SEPEDA MOTORHONDA SUPRA X 125 TAHUN 2009 - Sudrajat, Surya Catur (Jurnal Nosel, 2014)
The purpose of this research are to investigate: (1)The effect of using fixed and swirl electric turbo to exhaust gas emissions level of CO and HC on Honda Supra X 125 2009 motorcycle. (2) The effect of using modified of air filter to exhaust gas emissions level of CO and HC on Honda Supra X 125 2009 motorcycle. (3) The effect of using electric turbo and modified of air filter to exhaust gas emissions level of CO and HC on Honda Supra X 125 2009 motorcycle. (4) The lowest exhaust gas emissions level of CO and HC on Honda Supra X 125 2009 motorcycle. The method which used in this research was experimental method. The population  in this research were Honda Supra X 125 2009 motorcycle and sample was Honda Supra X 125 2009 motorcycle with JB91E1802814 engine number. Techniques of data analysis used descriptive data analysis. Based on this researchcan be concluded: (1) In standard condition, the emissions gas level of CO was 2.530% and the emissions gas level of HC was 1169 ppm. In the using of fixed electric turbo, the emissions gas level of CO was 2.199% and the emissions gas level of HC was 1093.33 ppm. So the reduced of the emissions gas level of CO was 0.331% and the emissions gas level of HC was 75.67 ppm. While in the using of swirl electric turbo, the emissions gas level of CO was 1.870% and the emissions gas level of HC was 823.33 ppm. So the reduced of the emissions gas level of CO was 0.66% and the emissions gas level of HC was 245.67 ppm. (2) In the using of modified air filter, the emissions gas level of CO was 1.472% and the emissions gas level of HC was 602 ppm. So the reduced of the emissions gas level of CO was 1.058% and the emissions gas level of HC was 602 ppm. (3) In the using of fixed electric turbo and modified of air filter, the emissions gas level of CO was 1.403% and the emissions gas level of HC was 403.33 ppm. So the reduced of the emissions gas level of CO was 1.127% and the emissions gas level of HC was 765.67 ppm. While in the using of swirl electric turbo and modified of air filter, the emissions gas level of CO was 0.946% and the emissions gas level of HC was 374.33 ppm. So the reduced of the emissions gas level of CO was 1.584% and the emissions gas level of HC was 794.67 ppm. (4) The lowest exhaust gas emissions level of CO and HC on Honda Supra X 125 2009 motorcycle at the using of swirl electric turbo and modified of air filter.